Binder for titanium concentrate briquetting and preparation method thereof, titanium concentrate pellets and preparation method thereof, metallized pellets

By using a composite organic binder composed of cellulose polymer, polyvinyl acetal and yttrium alginate, the compressive strength and metallization rate of titanium concentrate pellets are improved, and the low strength and powderization rate of pellets are solved. The problem of high and low titanium slag grades has achieved a high-efficiency and low-energy consumption titanium slag smelting process.

CN116144925BActive Publication Date: 2025-02-11SICHUAN LOMON MINING & METALLURGY +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310168701.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-24
Publication Date
2025-02-11
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

The prior art has problems in the titanium concentrate smelting process, which has low pellet strength, high powdering rate and low titanium slag grade, and has a long smelting cycle, resulting in low production efficiency and high energy consumption.

Method used

Using a composite organic binder composed of cellulose polymer, polyvinyl acetal and sodium alginate, the pellet-forming performance and resistance of the pellets are enhanced by improving the hydrophilicity of the surfaces of titanium concentrate and carbonaceous reducing agent. Pressure strength, reduce the powdering rate, and perform pellet preparation under low temperature drying conditions.

Benefits of technology

The dry ball compressive strength and metallization rate of titanium concentrate pellets have been significantly improved, the powdering rate and energy consumption have been reduced, the titanium slag smelting cycle has been shortened, and the production efficiency and product quality have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004097144890000011
    Figure HDA0004097144890000011
Patent Text Reader

Abstract

The present invention provides a binder for titanium concentrate briquetting and a preparation method thereof, titanium concentrate pellets and a preparation method thereof, and metallized pellets, which relate to the technical field of titanium slag smelting. The binder for titanium concentrate briquetting comprises the following components: cellulose polymer, polyvinyl acetal and sodium alginate, wherein the mass ratio of the three is 40-60:5-15:10-30. The present invention solves the technical problems of low strength of titanium concentrate pellets and high powdering rate of pellets during drying and reduction in the prior art, and achieves the technical effect that the binder is not only easy to preserve, but also the titanium concentrate pellets prepared have high strength and low powdering rate, and at the same time, no impurities are introduced in the titanium slag smelting process, which is conducive to the production of high-quality titanium slag products and improves the grade of titanium slag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium slag smelting, and in particular to a binder for titanium concentrate briquetting and a preparation method thereof, titanium concentrate pellets and a preparation method thereof, and metallized pellets. Background Art

[0002] Titanium slag smelting is a process in which titanium concentrate is added to an electric furnace in the form of powder or pellets together with a reducing agent. The ilmenite is decomposed into titanium oxide and iron oxide. The iron oxide is selectively reduced to metallic iron, and the titanium oxide is enriched in the slag. The titanium slag and metallic iron are effectively separated through the difference in specific gravity and melting point.

[0003] At present, in the production process of titanium slag, large-scale titanium slag electric furnaces are usually used to smelt fine-grained titanium concentrate, which mainly faces the following problems: (1) The addition of fine-grained titanium concentrate increases the difficulty of titanium slag smelting and reduces the recovery rate of titanium resources. With the in-depth development of vanadium-titanium magnetite mines in Panzhihua area, the easy-to-develop extra-surface ores are becoming increasingly exhausted, and the development of titanium resources has shifted to the internal ores with low weathering degree and poor selectivity. The internal ores are relatively hard, and ilmenite and gangue minerals are closely coexisting. In order to fully dissociate ilmenite, the grinding fineness of the ore must be increased. Therefore, the particle size of the titanium concentrate product becomes finer, and the fine-grained titanium concentrate particles are more and more fine. Small size will cause poor air permeability of raw materials, resulting in serious foam slag during the smelting process, causing energy loss and making the smelting process difficult to carry out. In addition, a part of the fine-grained titanium concentrate will be sucked into the dust removal flue after entering the electric furnace, resulting in the formation of dust removal ash, which will greatly reduce the titanium recovery rate and affect the titanium slag output; (2) In the titanium slag smelting electric furnace, the first reaction is the decomposition reaction of ilmenite, followed by the reduction reaction of iron oxides, and finally the separation of titanium and iron. Since these reactions all occur in the titanium slag electric furnace, the smelting cycle of large titanium slag electric furnaces is relatively long, generally 6 to 12 hours, resulting in reduced production efficiency and greatly increased power consumption. If the decomposition reaction and reduction reaction of the titanium concentrate are completed before the electric furnace smelting, and only titanium and iron separation is carried out in the electric furnace, the production efficiency will be effectively improved.

[0004] In order to solve the above problems, scientific researchers have conducted a lot of research and practice in the briquetting of titanium concentrate. The binders used are mainly divided into inorganic binders (such as bentonite and water glass, etc.) and organic binders (such as cellulose polymers and starch, etc.). Most of these binders are based on the production experience of iron concentrate pellets. However, there are significant differences in the physical and chemical properties and phase structures of titanium concentrate and iron concentrate. Iron concentrate is usually recovered from iron ore by magnetic separation, while titanium concentrate is usually recovered from the iron tailings of vanadium-titanium magnetite by flotation. Conventional flotation agents are all hydrophobic, making it difficult to pelletize titanium concentrate. This makes conventional binders often lead to problems such as low pellet strength, high pulverization rate and low titanium slag grade when used in titanium concentrate briquetting.

[0005] The invention patent with application publication number CN101649392 B discloses a method for pressing titanium concentrate into pellets and a pelletizing binder. The binder used is a composite binder composed of a liquid part and a solid part. The main technical feature is that titanium concentrate powder with a size of -0.075 mm and a proportion of more than 15 wt% is evenly mixed with 2% to 4% of the composite binder and 5% to 20% of the carbonaceous reducing agent, and then pressed into pellets with a particle size of 20 to 60 mm, and then dried at a temperature of 150 to 350°C for 60 to 180 minutes. The amount of binder added in this process is relatively high, which leads to an increase in the cost of pressing pellets. At the same time, the drying temperature of the raw balls is high and the drying time is long, which is not conducive to improving production efficiency. The invention patent with application publication number CN102399994 B discloses a method for smelting titanium slag. The binder used is a mixed binder of an inorganic binder and an organic binder, and the mass content of the organic binder is not less than 50%. The main technical feature is that the titanium concentrate powder is evenly mixed with 0.5% to 3.5% of the binder and 10% to 25% of the carbonaceous reducing agent, and then pressed into balls, and then dried at a temperature of 200 to 350°C for 30 to 90 minutes, and then pre-reduced in a ring furnace or a rotary hearth furnace. The pre-reduction temperature is controlled between 1300 and 1450°C, the pre-reduction time is 30 to 70 minutes, and the metallization rate is 55% to 85%. The inorganic binder used in this process contains impurities such as SiO2, Al2O3, MgO and CaO, which affect the quality of the titanium slag product. At the same time, the drying temperature and the pre-reduction temperature are both high, resulting in increased energy consumption. The invention patent with application publication number CN103898317 B discloses a binder composition for titanium concentrate pelletizing and a method for preparing titanium concentrate pellets. The binder composition used contains cellulose-based polymers, calcium lignin sulfonate, calcium sugar, and starch. The main technical feature is that -0.074mm titanium concentrate powder is evenly mixed with 2% to 3% of a binder and then pelletized, and then dried at a temperature of 150 to 250°C for 20 to 40 minutes. The amount of binder added in this process is relatively large, and no carbonaceous reducing agent is added to the pellets. Therefore, the effect of pre-reduction of the pellets cannot be achieved and the production cycle of titanium slag cannot be shortened. The invention patent with application publication number CN108374084 B discloses a production process for high-strength carbon-containing titanium concentrate pellets. The binder used is a composite binder, which is obtained by mixing an organic binder dry basis with bentonite in a mass ratio of 6 to 100:100. The amount of the binder added is 0.05% to 0.1% of the mass of the titanium concentrate. The main technical feature is that the titanium concentrate powder ore is evenly mixed with the composite binder and 10% to 20% of a carbonaceous reducing agent, and then the pellets with a particle size of 10 to 18 mm are formed by disc pressing, and then dried at a temperature of 105 to 350°C for 45 to 120 minutes. The composite binder of the process contains bentonite that is easy to introduce impurities. At the same time, the internal carbon pellets produced by the process have limited effect on reducing the energy consumption of titanium slag smelting and improving production efficiency.

[0006] In the process of large-scale titanium slag electric furnace smelting, the height difference of material transportation is large, generally exceeding 20 meters. Titanium concentrate is used in titanium slag smelting in the form of pellets. During the material transportation process, the titanium concentrate pellets must have a certain strength. For example, when the pellets enter the roasting equipment after drying, the pellet strength is generally required to be greater than 200N. After roasting, the pellets need to be transported to the top of the electric furnace by belts, and then the pellets fall from the top of the electric furnace into the molten pool for melting. Generally, the pellet strength is required to be greater than 1200N. At the same time, if the titanium concentrate pellets are to achieve a good pre-reduction effect, a certain proportion of carbonaceous reducing agent must be added to the titanium concentrate pellets. The addition of carbon will reduce the pellet strength and increase the powdering rate of the pellets during the drying and reduction process.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] One of the purposes of the present invention is to provide a binder for titanium concentrate pelletizing, which can improve the dry ball compressive strength of titanium concentrate pellets, reduce the pulverization rate of titanium concentrate pellets, will not introduce impurities during the titanium slag smelting process, and is conducive to the production of high-quality titanium slag products.

[0009] The second object of the present invention is to provide a method for preparing a binder for titanium concentrate briquetting, which has a simple process, high efficiency, high product quality rate and is suitable for factory production.

[0010] A third object of the present invention is to provide a titanium concentrate pellet having high compressive strength and low pulverization rate.

[0011] A fourth object of the present invention is to provide a method for preparing titanium concentrate pellets, which has a simple process, high efficiency, high product quality rate, and is suitable for factory production.

[0012] A fifth object of the present invention is to provide a metallized pellet having high compressive strength and high metallization rate.

[0013] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0014] In a first aspect, a binder for titanium concentrate briquetting comprises the following components:

[0015] Cellulose polymer, polyvinyl acetal, and sodium alginate;

[0016] The mass ratio of cellulose polymer, polyvinyl acetal and sodium alginate is 40-60:5-15:10-30.

[0017] Furthermore, the mass ratio of the cellulose polymer, polyvinyl acetal and sodium alginate is 50:10:20;

[0018] Preferably, the cellulose polymer comprises at least one of carboxymethyl cellulose, carboxyethyl cellulose and hydroxypropyl cellulose;

[0019] Preferably, the polyvinyl acetal includes at least one of polyvinyl formal, polyvinyl acetal and polyvinyl butyral.

[0020] In a second aspect, a method for preparing a binder for titanium concentrate briquetting as described in any one of the above items comprises the following steps:

[0021] After mixing the components in proportion, a thickening emulsion is added to obtain a binder for pressing titanium concentrate into balls;

[0022] Preferably, the amount of the thickening emulsion added accounts for 5% to 20% of the mass of the binder for titanium concentrate briquetting;

[0023] Preferably, the amount of the thickening emulsion added accounts for 10% of the mass of the binder for titanium concentrate briquetting.

[0024] In a third aspect, a titanium concentrate pellet comprises the binder for titanium concentrate pelletizing as described in any one of the above items.

[0025] In a fourth aspect, a method for preparing titanium concentrate pellets comprises the following steps:

[0026] The titanium concentrate pelletizing binder is mixed with the titanium concentrate and pelletized to obtain the titanium concentrate pellets.

[0027] Furthermore, the method for preparing the titanium concentrate pellets comprises the following steps:

[0028] (a) mixing titanium concentrate and a carbonaceous reducing agent to obtain a mixed material;

[0029] (b) The mixed material of step (a), the titanium concentrate briquetting binder and water are mixed and briquetting is performed to obtain the titanium concentrate pellets.

[0030] Furthermore, in step (a), the mass ratio of the titanium concentrate to the carbonaceous reducing agent is 90:10-25;

[0031] Preferably, the proportion of particles smaller than 0.075 mm in the titanium concentrate is greater than 70%;

[0032] Preferably, the carbonaceous reducing agent includes at least one of anthracite, blue charcoal and coke;

[0033] Preferably, the carbonaceous reducing agent is anthracite;

[0034] Preferably, the proportion of particles smaller than 1 mm in the anthracite is greater than 80%.

[0035] Furthermore, in step (b), the mass ratio of the mixed material to the binder for briquetting the titanium concentrate is 100:0.4-1;

[0036] Preferably, the water accounts for 5% to 9% of the mass of the mixed material;

[0037] Preferably, the ball pressing equipment comprises a high-pressure ball press;

[0038] Preferably, the process parameters of the ball pressing include:

[0039] Roller diameter 290mm;

[0040] and / or, output 1-3 t / h;

[0041] and / or, roller surface pressure 20-30 MPa;

[0042] And / or, the pressure is maintained for 0.5 to 1 second.

[0043] A fifth aspect provides a metallized pellet obtained by roasting the titanium concentrate pellet described above.

[0044] Furthermore, the calcination temperature is 900-1300°C, and the calcination time is 0.5-2h;

[0045] Preferably, the step of drying the titanium concentrate pellets is further included before roasting;

[0046] Preferably, the drying temperature is 120-180° C., and the drying time is 0.5-2 h.

[0047] Compared with the prior art, the present invention has at least the following beneficial effects:

[0048] The binder for titanium concentrate pelletizing provided by the present invention contains a surfactant. With the coordinated cooperation of various components and their mass ratios, the hydrophilicity of the surfaces of titanium concentrate and carbonaceous reducing agent (such as anthracite) can be increased, thereby greatly improving the pelletizing performance of titanium concentrate pellets, improving the dry ball compressive strength of titanium concentrate pellets and reducing the pulverization rate, so that the pulverization rate of the pellets during the drying process is less than 1%, and the pulverization rate of the pellets during the pre-reduction roasting process is less than 2%, thereby significantly improving production efficiency; the binder of the present invention is a composite organic binder, which can volatilize during the pre-reduction roasting of titanium concentrate pellets, so that impurities will not be introduced during the titanium slag smelting process, which is conducive to the production of high-quality titanium slag products; compared with the high-temperature drying of the binder in the prior art, the binder of the present invention is conducive to low-temperature drying, and the amount of water added when mixing the materials is low, so the temperature when drying the raw pellets is low, the drying time is short, and energy is saved.

[0049] The method for preparing the binder for titanium concentrate briquetting provided by the invention has simple process, high efficiency, high product quality rate and is suitable for factory production.

[0050] The titanium concentrate pellets provided by the present invention have high compressive strength and low pulverization rate. The strength of the pellets after drying is greater than 300N. After pre-reduction and roasting treatment, metallized pellets with a metallization rate of 70% to 90% and a strength greater than 1500N can be obtained, which shortens the titanium slag smelting cycle by more than 60% and significantly reduces power consumption. It can not only improve the titanium slag production capacity, but also effectively reduce the titanium slag production cost, and is suitable for industrial production.

[0051] The method for preparing titanium concentrate pellets provided by the invention has simple process, high efficiency, high product quality rate and is suitable for factory production.

[0052] The metallized pellets provided by the present invention have high compressive strength and high metallization rate. The pellet strength is greater than 1500N, which fully meets the requirements for pellet transportation in the titanium slag production process. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0054] Figure 1 This is a flow chart of the pre-reduction treatment of titanium concentrate provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0055] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] According to a first aspect of the present invention, there is provided a binder for briquetting titanium concentrate, comprising the following components:

[0057] Cellulose polymer, polyvinyl acetal, and sodium alginate;

[0058] The mass ratio of cellulose polymer, polyvinyl acetal and sodium alginate is 40-60:5-15:10-30.

[0059] The binder for titanium concentrate pelletizing provided by the present invention contains a surfactant. With the coordinated cooperation of various components and their mass ratios, the hydrophilicity of the surfaces of titanium concentrate and carbonaceous reducing agent (such as anthracite) can be increased, thereby greatly improving the pelletizing performance of titanium concentrate pellets, improving the dry ball compressive strength of titanium concentrate pellets and reducing the pulverization rate, so that the pulverization rate of the pellets during the drying process is less than 1%, and the pulverization rate of the pellets during the pre-reduction roasting process is less than 2%, thereby significantly improving production efficiency; the binder of the present invention is a composite organic binder, which can volatilize during the pre-reduction roasting of titanium concentrate pellets, so that impurities will not be introduced during the titanium slag smelting process, which is conducive to the production of high-quality titanium slag products; compared with the high-temperature drying of the binder in the prior art, the binder of the present invention is conducive to low-temperature drying, and the amount of water added when mixing the materials is low, so the temperature when drying the raw pellets is low, the drying time is short, and energy is saved.

[0060] In a preferred embodiment, the mass ratio of cellulose polymer, polyvinyl acetal and sodium alginate can be 50:10:20, and the components and their mass ratio can achieve better synergistic effect, further improve the pellet strength of titanium concentrate and reduce the pellet powderization rate, thereby further improving production efficiency, and can further reduce the drying temperature and drying time of the pellets, which is beneficial to saving energy.

[0061] In a preferred embodiment, the cellulose polymer includes but is not limited to at least one of carboxymethyl cellulose, carboxyethyl cellulose and hydroxypropyl cellulose.

[0062] In a preferred embodiment, the polyvinyl acetal includes but is not limited to at least one of polyvinyl formal, polyvinyl acetal and polyvinyl butyral.

[0063] The binder for titanium concentrate briquetting provided by the present invention solves the technical problems in the prior art that the titanium concentrate pellets obtained by briquetting have low strength, high pulverization rate, and low grade of titanium slag obtained by smelting, and achieves the technical effects that the titanium concentrate pellets have high strength, low pulverization rate, low drying temperature, and no introduction of impurities.

[0064] According to a second aspect of the present invention, there is provided a method for preparing a binder for titanium concentrate briquetting as described in any one of the above, comprising the following steps:

[0065] After the components are mixed in proportion, a thickening emulsion is added to obtain a binder for titanium concentrate pelletizing.

[0066] In a preferred embodiment, the amount of thickening emulsion added can account for 5% to 20% of the mass of the binder for titanium concentrate briquetting, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 18%, 20%, but not limited to this, and can be further preferably 10%, which is more conducive to improving the actual performance of the binder.

[0067] The binder provided by the invention is composed of a solid part and a liquid part, and the preparation method comprises: firstly mixing cellulose polymer, polyvinyl acetal and sodium alginate uniformly, then adding a thickening emulsion while stirring and mixing uniformly to obtain an organic binder.

[0068] The method for preparing the binder for titanium concentrate briquetting provided by the invention has simple process, high efficiency, high product quality rate and is suitable for factory production.

[0069] According to a third aspect of the present invention, there is provided a titanium concentrate pellet comprising any one of the above-mentioned binders for titanium concentrate pelletizing.

[0070] Pelletizing can improve the permeability of the charge, reduce the generation of foamy slag, optimize the condition of the titanium slag electric furnace, and at the same time reduce the amount of titanium concentrate entering the dust removal ash and increase the recovery rate of titanium.

[0071] The titanium concentrate pellets provided by the present invention have high compressive strength and low pulverization rate. The strength of the pellets after drying is greater than 300N. After pre-reduction and roasting treatment, metallized pellets with a metallization rate of 70% to 90% and a strength greater than 1500N can be obtained, which shortens the titanium slag smelting cycle by more than 60% and significantly reduces power consumption. It can not only improve the titanium slag production capacity, but also effectively reduce the titanium slag production cost, and is suitable for industrial production.

[0072] According to a fourth aspect of the present invention, there is provided a method for preparing titanium concentrate pellets, comprising the following steps:

[0073] The titanium concentrate is mixed with a binder for briquetting and the titanium concentrate is briquetting to obtain titanium concentrate pellets.

[0074] The method for preparing titanium concentrate pellets provided by the invention has simple process, high efficiency, high product quality rate and is suitable for factory production.

[0075] In a preferred embodiment, the method for preparing titanium concentrate pellets comprises the following steps:

[0076] (a) mixing titanium concentrate and a carbonaceous reducing agent to obtain a mixed material;

[0077] (b) The mixed material of step (a), a binder for titanium concentrate briquetting and water are mixed and briquetting is performed to obtain titanium concentrate pellets.

[0078] In the present invention, the titanium concentrate and the carbonaceous reducing agent are first mixed evenly, and then a binder is added and pressed into balls to form pellets. This allows the titanium concentrate and the carbonaceous reducing agent to be in uniform contact, which is beneficial to the reduction reaction in the subsequent pre-reduction roasting process. However, if the titanium concentrate, the binder and the carbonaceous reducing agent are mixed at the same time, local wrapping of the binder and the carbonaceous reducing agent, or the binder and the titanium concentrate, is likely to occur, resulting in uneven mixing and affecting the subsequent pre-reduction roasting effect.

[0079] In a preferred embodiment, in step (a), the proportion of particles with a size less than 0.075 mm in the titanium concentrate is greater than 70%; the mass ratio of the titanium concentrate and the carbonaceous reducing agent can be 90:10-25, and its typical but non-limiting mass ratio is, for example, 90:10, 90:15, 90:20, 90:25, but not limited thereto, which is more conducive to improving the effect of pre-reduction roasting of titanium concentrate pellets.

[0080] In the present invention, the titanium concentrate particle size is less than 0.075 mm, accounting for more than 70%, of which the TiO2 content is greater than 48%, and the Fe content is less than 35%. At present, the -200 mesh particle size accounts for more than 70% of the titanium concentrate in Panzhihua area. Therefore, the titanium concentrate raw material does not need to be ground and can be directly pressed into balls.

[0081] In a preferred embodiment, the carbonaceous reducing agent includes but is not limited to at least one of anthracite, lignite and coke, and anthracite is further preferred, which is more conducive to improving the effect of pre-reduction roasting of titanium concentrate pellets.

[0082] In the present invention, the carbonaceous reducing agent can be one of anthracite, lignite and coke, and can be further preferably anthracite, wherein the fixed carbon content in the anthracite is greater than 80%, and the ash content is less than 10%. The main components of the ash in the anthracite are impurities such as Ca and Mg. Too high ash content will affect the quality of titanium slag.

[0083] In a preferred embodiment, the proportion of particles smaller than 1 mm in the anthracite is greater than 80%.

[0084] The binder provided by the present invention is mixed with a carbonaceous reducing agent to produce titanium concentrate pellets with high strength. The strength of the pellets after drying is greater than 300N, and the strength of the pellets after pre-reduction and roasting is greater than 1500N, which can fully meet the requirements for pellet transportation in the titanium slag production process.

[0085] In a preferred embodiment, in step (b), the mass ratio of the mixed material and the binder for titanium concentrate briquetting can be 100:0.4-1, and its typical but non-limiting mass ratio is, for example, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, and 100:1.

[0086] In a preferred embodiment, in step (b), water can account for 5% to 9% of the mass of the mixed material, for example, 5%, 6%, 7%, 8%, 9%, but not limited to this. Adding water during the ball pressing process is more conducive to improving the balling properties.

[0087] In a preferred embodiment, the ball pressing equipment includes but is not limited to a high-pressure ball press, wherein the ball pressing process parameters include but are not limited to: roller skin diameter 290 mm; and / or, output 1 to 3 t / h; and / or, roller surface pressure 20 to 30 MPa; and / or, pressure holding time 0.5 to 1 s.

[0088] The pelletizing process parameters of the present invention are more conducive to improving the pelletizing performance of titanium concentrate pellets, further improving the strength of the pellets and reducing the pulverization rate.

[0089] According to a fifth aspect of the present invention, there is provided a metallized pellet obtained by roasting the titanium concentrate pellet.

[0090] The metallized pellets provided by the present invention have high compressive strength and high metallization rate. The pellet strength is greater than 1500N, which fully meets the requirements for pellet transportation in the titanium slag production process.

[0091] In a preferred embodiment, the calcination (pre-reduction) temperature can be 900-1300°C, and typical but non-limiting temperatures are, for example, 900°C, 1000°C, 1100°C, 1200°C, and 1300°C. The calcination time can be 0.5-2h, and typical but non-limiting times are, for example, 0.5h, 1h, 1.5h, and 2h, which is more conducive to improving the strength of the pellets after pre-reduction and improving the metallization rate of the pellets. The calcination of the pellets can be carried out in a small vertical furnace, and the powderization rate of the pellets in the process is less than 2%.

[0092] In a preferred embodiment, the metallized pellets are added into a 100KVA electric furnace, and then a small amount of carbonaceous reducing agent is added into the electric furnace, which can strengthen the reducing atmosphere in the electric furnace and improve the grade of titanium slag.

[0093] In a preferred embodiment, the step of drying the titanium concentrate pellets is further included before roasting;

[0094] The drying temperature can be 120-180°C, and typical but non-limiting temperatures are, for example, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, and 180°C. The drying time can be 0.5-2h, and typical but non-limiting times are 0.5h, 1.5h, and 2h. The drying can be carried out in a chain plate dryer. The compressive strength of the dry ball after drying is greater than 300N, and the pulverization rate of the pellets during the drying process is less than 1%.

[0095] The metallized pellets provided by the present invention have a metallization rate of 70% to 90%, and a pellet strength greater than 1500N. They can shorten the titanium slag smelting cycle by more than 60%, significantly reduce power consumption, and can both increase the titanium slag production capacity and effectively reduce the titanium slag production cost, and are suitable for industrial production applications.

[0096] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0097] Example 1

[0098] A method for preparing a binder for titanium concentrate briquetting comprises the following steps:

[0099] Carboxymethyl cellulose, polyvinyl formal and sodium alginate are mixed evenly in a mass ratio of 50:10:20, and then a thickening emulsion is added while stirring to obtain a binder;

[0100] The added amount of the thickening emulsion accounts for 10% of the mass of the adhesive.

[0101] The binder obtained in this example is used to prepare metallized pellets for titanium slag smelting. Figure 1 , including the following steps:

[0102] (1) 9 kg of titanium concentrate with a particle size of less than 0.074 mm and a proportion of more than 70% and 2 kg of anthracite with a particle size of less than 1 mm and a proportion of more than 80% were uniformly mixed for 5 minutes to obtain a mixed material, and then 80 g of the binder of the present embodiment was added and uniformly mixed for 10 minutes, and finally 800 mL of water was added and uniformly mixed for 5 minutes to obtain a pelletizing material;

[0103] (2) The pelletizing material is continuously pressed into pellets (pressed into pellets) on a 290 type high pressure pellet press, wherein the pressure of the pellet press is 25 MPa and the pressure holding time is 0.7 s, to obtain raw pellets with a particle size of 25 to 30 mm, and then the raw pellets are sent to a HJWD6 type chain plate dryer for drying, wherein the drying temperature is 140° C. and the drying time is 60 min, to obtain dry pellets, whose compressive strength can reach 400 N;

[0104] (3) The dried pellets (dry pellets) are transported into a vertical furnace and pre-reduced and roasted at 1200° C. for 60 min to obtain metallized pellets (pre-reduced pellets) having a compressive strength of 1850 N and a metallization rate of 87.5%;

[0105] (4) The metallized pellets are added to a 100KVA electric furnace. In order to strengthen the reducing atmosphere in the electric furnace, a small amount of carbonaceous reducing agent is added to the electric furnace to maintain the furnace temperature at 1500-1700°C (electric furnace smelting). Finally, a product with a titanium slag grade of 87.2% is obtained, and the production cycle is 30 minutes.

[0106] Example 2

[0107] The difference between this embodiment and embodiment 1 is that the binder of embodiment 1 is used to prepare metallized pellets for titanium slag smelting, comprising the following steps:

[0108] (1) 9 kg of titanium concentrate with a particle size of less than 0.074 mm and a proportion of more than 70% and 2.5 kg of anthracite with a particle size of less than 1 mm and a proportion of more than 80% were uniformly mixed for 5 minutes, then 100 g of a binder was added and uniformly mixed for 10 minutes, and finally 800 mL of water was added and uniformly mixed for 5 minutes to obtain a pelletizing material;

[0109] (2) The pelletizing material is continuously pressed on a 290 type high pressure pelletizing machine, wherein the pressure of the pelletizing machine is 30 MPa, and the pressure holding time is 1 second, to obtain raw pellets with a particle size of 25 to 30 mm, and then the raw pellets are sent to a HJWD6 type chain plate dryer for drying, wherein the drying temperature is 160° C., and the drying time is 90 minutes, to obtain dry pellets, whose compressive strength can reach 420N;

[0110] (3) The dried pellets (dry pellets) are transported to a vertical furnace and calcined at 1300° C. for 90 min to obtain metallized pellets with a compressive strength of 2100 N and a metallization rate of 92.5%;

[0111] (4) The metallized pellets are added to a 100KVA electric furnace. In order to strengthen the reducing atmosphere in the furnace, a small amount of carbonaceous reducing agent is added to the furnace to maintain the furnace temperature at 1500-1700°C. Finally, a product with a titanium slag grade of 89.3% is obtained, and the production cycle is 25 minutes.

[0112] Example 3

[0113] The difference between this embodiment and embodiment 1 is that the binder of embodiment 1 is used to prepare metallized pellets for titanium slag smelting, comprising the following steps:

[0114] (1) 9 kg of titanium concentrate with a particle size of less than 0.074 mm and a proportion of more than 70% and 1 kg of anthracite with a particle size of less than 1 mm and a proportion of more than 80% were uniformly mixed for 5 minutes, then 50 g of a binder was added and uniformly mixed for 10 minutes, and finally 700 mL of water was added and uniformly mixed for 5 minutes to obtain a pelletizing material;

[0115] (2) The pelletizing material is continuously pressed on a 290 type high pressure pelletizing machine, wherein the pressure of the pelletizing machine is 20 MPa, the pressure holding time is 0.7 s, and raw pellets with a particle size of 25 to 30 mm are obtained. The raw pellets are then sent to a HJWD6 type chain plate dryer for drying, wherein the drying temperature is 140° C., the drying time is 80 min, and dry pellets are obtained, the compressive strength of which can reach 330 N;

[0116] (3) The dried pellets (dry pellets) are transported into a vertical furnace and calcined at 1100° C. for 60 min to obtain metallized pellets with a compressive strength of 1620 N and a metallization rate of 73.42%;

[0117] (4) The metallized pellets are added to a 100KVA electric furnace. In order to strengthen the reducing atmosphere in the furnace, a small amount of carbonaceous reducing agent is added to the furnace to maintain the furnace temperature at 1500-1700°C. Finally, a product with a titanium slag grade of 85.7% is obtained, and the production cycle is 45 minutes.

[0118] Example 4

[0119] The difference between this embodiment and embodiment 1 is that the binder of embodiment 1 is used to prepare metallized pellets for titanium slag smelting, comprising the following steps:

[0120] (1) 9 kg of titanium concentrate with a particle size of less than 0.074 mm and a proportion of more than 70% and 1.5 kg of anthracite with a particle size of less than 1 mm and a proportion of more than 80% were uniformly mixed for 5 minutes, then 70 g of a binder was added and uniformly mixed for 10 minutes, and finally 750 mL of water was added and uniformly mixed for 5 minutes to obtain a pelletizing material;

[0121] (2) The pellets are continuously pressed on a 290 type high pressure pellet press, wherein the pressure of the pellet press is 25 MPa, the pressure holding time is 0.7 s, and raw pellets with a particle size of 25 to 30 mm are obtained. The raw pellets are then sent to a HJWD6 type chain plate dryer for drying, wherein the drying temperature is 150° C., the drying time is 75 min, and dry pellets are obtained, the compressive strength of which can reach 380 N.

[0122] (3) The dried pellets (dry pellets) are transported into a vertical furnace and calcined at 1200° C. for 120 min to obtain metallized pellets with a compressive strength of 1725 N and a metallization rate of 82.78%;

[0123] (4) The metallized pellets were added to a 100KVA electric furnace. In order to strengthen the reducing atmosphere in the furnace, a small amount of carbonaceous reducing agent was added to the furnace to maintain the furnace temperature at 1500-1700°C. Finally, a product with a titanium slag grade of 86.3% was obtained, and the production cycle was 37 minutes.

[0124] Example 5

[0125] The difference between this embodiment and embodiment 1 is that the mass ratio of carboxymethyl cellulose, polyvinyl formal and sodium alginate is 40:15:25, and the rest is the same as in embodiment 1, and a binder for titanium concentrate briquetting is obtained. Metallized pellets are prepared according to the same method as in embodiment 1 and used for titanium slag smelting. The compressive strength of the obtained dried pellets can reach 415N, the compressive strength of the obtained metallized pellets can reach 1870N, the metallization rate is 88.4%, and finally a product with a titanium slag grade of 87.9% is obtained, and the production cycle is 30min.

[0126] Example 6

[0127] The difference between this embodiment and embodiment 1 is that the mass ratio of carboxymethyl cellulose, polyvinyl formal and sodium alginate is 45:5:30, and the rest is the same as in embodiment 1, and a binder for titanium concentrate briquetting is obtained. Metallized pellets are prepared according to the same method as in embodiment 1 and used for titanium slag smelting. The compressive strength of the obtained dried pellets can reach 432N, the compressive strength of the obtained metallized pellets can reach 1935N, the metallization rate is 87.8%, and finally a product with a titanium slag grade of 87.5% is obtained, and the production cycle is 30min.

[0128] Example 7

[0129] The difference between this embodiment and embodiment 1 is that the mass ratio of carboxymethyl cellulose, polyvinyl formal and sodium alginate is 50:15:15, and the rest is the same as in embodiment 1, and a binder for titanium concentrate briquetting is obtained. Metallized pellets are prepared according to the same method as in embodiment 1 and used for titanium slag smelting. The compressive strength of the obtained dried pellets can reach 384N, the compressive strength of the obtained metallized pellets can reach 1720N, the metallization rate is 86.9%, and finally a product with a titanium slag grade of 86.5% is obtained, and the production cycle is 30min.

[0130] Example 8

[0131] The difference between this embodiment and embodiment 1 is that the mass ratio of carboxymethyl cellulose, polyvinyl formal and sodium alginate is 55:15:10, and the rest is the same as in embodiment 1, and a binder for titanium concentrate briquetting is obtained. Metallized pellets are prepared according to the same method as in embodiment 1 and used for titanium slag smelting. The compressive strength of the obtained dried pellets can reach 377N, the compressive strength of the obtained metallized pellets can reach 1775N, the metallization rate is 87.1%, and finally a product with a titanium slag grade of 86.8% is obtained, and the production cycle is 30min.

[0132] Example 9

[0133] The difference between this embodiment and embodiment 1 is that the mass ratio of carboxymethyl cellulose, polyvinyl formal and sodium alginate is 60:10:10, and the rest is the same as in embodiment 1, and a binder for titanium concentrate briquetting is obtained. Metallized pellets are prepared according to the same method as in embodiment 1 and used for titanium slag smelting. The compressive strength of the obtained dried pellets can reach 350N, the compressive strength of the obtained metallized pellets can reach 1695N, the metallization rate is 87.4%, and finally a product with a titanium slag grade of 87.1% is obtained, and the production cycle is 30min.

[0134] Example 10

[0135] The difference between this embodiment and embodiment 1 is that in this embodiment, carboxymethyl cellulose is replaced by an equal amount of carboxyethyl cellulose, and the rest is the same as in embodiment 1, to obtain a binder for titanium concentrate briquetting, and metallized pellets are prepared according to the same method as in embodiment 1 for titanium slag smelting. The compressive strength of the obtained dried pellets can reach 392N, the compressive strength of the obtained metallized pellets can reach 1800N, the metallization rate is 87.2%, and finally a product with a titanium slag grade of 86.9% is obtained, and the production cycle is 30min.

[0136] Embodiment 11

[0137] The difference between this embodiment and embodiment 1 is that in this embodiment, carboxymethyl cellulose is replaced with an equal amount of hydroxypropyl cellulose, and the rest is the same as in embodiment 1, to obtain a binder for titanium concentrate briquetting, and to prepare metallized pellets according to the same method as in embodiment 1 for titanium slag smelting. The compressive strength of the obtained dried pellets can reach 376N, the compressive strength of the obtained metallized pellets can reach 1820N, the metallization rate is 88.4%, and finally a product with a titanium slag grade of 87.7% is obtained, and the production cycle is 30min.

[0138] Example 12

[0139] The difference between this embodiment and embodiment 1 is that this embodiment replaces polyvinyl formal with an equal amount of polyvinyl acetal, and the rest is the same as embodiment 1, to obtain a binder for titanium concentrate briquetting, and to prepare metallized pellets according to the same method as in embodiment 1 for titanium slag smelting. The compressive strength of the obtained dried pellets can reach 406N, the compressive strength of the obtained metallized pellets can reach 1905N, the metallization rate is 86.8%, and finally a product with a titanium slag grade of 86.3% is obtained, and the production cycle is 30min.

[0140] Example 13

[0141] The difference between this embodiment and embodiment 1 is that this embodiment replaces polyvinyl formal with an equal amount of polyvinyl butyral, and the rest is the same as embodiment 1, to obtain a binder for titanium concentrate briquetting, and to prepare metallized pellets according to the same method as in embodiment 1 for titanium slag smelting. The compressive strength of the obtained dried pellets can reach 391N, the compressive strength of the obtained metallized pellets can reach 1875N, the metallization rate is 87.1%, and finally a product with a titanium slag grade of 86.7% is obtained, and the production cycle is 30min.

[0142] Embodiment 14

[0143] The difference between this embodiment and embodiment 1 is that in this embodiment, 9 kg of titanium concentrate is uniformly mixed with 80 g of binder, during which no anthracite is added, and no pre-reduction is performed. The obtained dry pellets (with a compressive strength of up to 520 N) are added to a 100KVA electric furnace, and 2 kg of anthracite is added to the electric furnace at the same time. The rest is the same as in embodiment 1, and finally a product with a titanium slag grade of 84.3% is obtained, and the production cycle is 120 minutes.

[0144] It can be seen that if the pre-reduction process is not carried out, the titanium slag smelting cycle will be greatly increased, seriously affecting the production efficiency.

[0145] Embodiment 15

[0146] The difference between this embodiment and embodiment 1 is that in this embodiment, 9 kg of titanium concentrate is uniformly mixed with 80 g of binder, and no anthracite is added during the process. In step (3), 2 kg of anthracite is added to the vertical furnace while the dried pellets (with a compressive strength of up to 520 N) are transported into the vertical furnace, and then pre-reduction roasting is carried out. The rest is the same as in embodiment 1. The compressive strength of the obtained metallized pellets is 2060 N, the metallization rate is 45.5%, and finally a product with a titanium slag grade of 85.2% is obtained. The production cycle is 80 min.

[0147] It can be seen that if the carbonaceous reducing agent (anthracite) and the pellets are mixed evenly during the pre-reduction process, metallized pellets with a lower metallization rate are obtained, which prolongs the production cycle of the titanium slag in the electric furnace.

[0148] Comparative Example 1

[0149] The difference between this comparative example and Example 1 is that the binder in this comparative example is bentonite, and the briquetting process for titanium concentrate comprises the following steps:

[0150] (1) 9 kg of titanium concentrate with a particle size of less than 0.074 mm and a proportion of more than 70% and 2 kg of anthracite with a particle size of less than 1 mm and a proportion of more than 80% were uniformly mixed for 5 minutes, 80 g of bentonite binder was added, and the mixture was uniformly mixed for 10 minutes, and finally 800 mL of water was added and uniformly mixed for 5 minutes to obtain a pelletizing material;

[0151] (2) The ball-making material is continuously pressed into balls on a 290 type high-pressure ball press, wherein the pressure of the ball press is 25 MPa and the pressure holding time is 0.7 s, to obtain raw balls with a particle size of 25 to 30 mm. The raw balls are then sent to a HJWD6 type chain plate dryer for drying, wherein the drying temperature is 140°C and the drying time is 60 min, to obtain dry pellets with a compressive strength of 70 N, which cannot meet the transportation requirements during the titanium slag production process.

[0152] Under the same conditions, the compressive strength of the pellets using the binder of the present invention can reach 400N.

[0153] Comparative Example 2

[0154] The difference between this comparative example and Example 1 is that the binder in this comparative example is bentonite, and the briquetting process for titanium concentrate comprises the following steps:

[0155] (1) 9 kg of titanium concentrate with a particle size of less than 0.074 mm and a proportion of more than 70% and 2 kg of anthracite with a particle size of less than 1 mm and a proportion of more than 80% were uniformly mixed for 5 minutes, 400 g of bentonite binder was added, and the mixture was uniformly mixed for 10 minutes, and finally 800 mL of water was added and uniformly mixed for 5 minutes to obtain a pelletizing material;

[0156] (2) The pelletizing material is continuously pressed on a 290 type high pressure pelletizing machine, wherein the pressure of the pelletizing machine is 25 MPa, the pressure holding time is 0.7 s, and raw pellets with a particle size of 25 to 30 mm are obtained. The raw pellets are then sent to a HJWD6 type chain plate dryer for drying, wherein the drying temperature is 140° C. and the drying time is 60 min to obtain dried pellets with a compressive strength of 210 N, which basically meets the transportation requirements in the titanium slag production process, but the pellet pulverization rate is greater than 3%;

[0157] (3) The dried pellets are transported into a vertical furnace and calcined at 1200° C. for 60 min to obtain metallized pellets with a compressive strength of 1780 N and a metallization rate of 84.3%;

[0158] (4) The metallized pellets are added to a 100KVA electric furnace. In order to strengthen the reducing atmosphere in the furnace, a small amount of carbonaceous reducing agent is added to the furnace to maintain the temperature in the furnace at 1500-1700°C. Finally, a product with a titanium slag grade of 81.4% is obtained, and the production cycle is 35 minutes.

[0159] It can be seen that by increasing the amount of bentonite binder added to 4% of the mixed material, the obtained pellet strength can meet the requirements of titanium slag production, but the pellet pulverization rate is relatively high. At the same time, bentonite will introduce impurity elements such as Ca, Mg, and Si, which will reduce the grade of titanium slag. In particular, the Ca element will seriously affect the application of titanium slag in the production of titanium dioxide by the chloride process.

[0160] Comparative Example 3

[0161] The difference between this comparative example and Example 1 is that the binder of this comparative example does not contain carboxymethyl cellulose, and the rest is the same as Example 1. The defect of the obtained binder is that the compressive strength of the dried pellets prepared by the binder is 216N, the compressive strength of the obtained metallized pellets is 1175N, the metallization rate is 87.3%, and the final product has a titanium slag grade of 86.8%. The production cycle is 30min. Although the metallization rate and the titanium slag grade are both up to standard, the compressive strength of the dried pellets and the metallized pellets is low and cannot meet the transportation requirements during the titanium slag production process.

[0162] Comparative Example 4

[0163] The difference between this comparative example and Example 1 is that the binder of this comparative example does not contain polyvinyl formal, and the rest is the same as Example 1. The defect of the obtained binder is that the compressive strength of the dried pellets prepared by the binder is 197N, the compressive strength of the obtained metallized pellets is 1042N, the metallization rate is 87.2%, and the final product has a titanium slag grade of 86.5%. The production cycle is 30min. Although the metallization rate and the titanium slag grade are both up to standard, the compressive strength of the dried pellets and the metallized pellets is low and cannot meet the transportation requirements during the titanium slag production process.

[0164] Comparative Example 5

[0165] The difference between this comparative example and Example 1 is that the binder of this comparative example does not contain sodium alginate, and the rest is the same as Example 1. The defect of the obtained binder is that the compressive strength of the dried pellets prepared by the binder is 151N, the compressive strength of the obtained metallized pellets is 842N, the metallization rate is 86.7%, and the final product with a titanium slag grade of 86.2% is obtained. The production cycle is 30min. Although the metallization rate and the titanium slag grade are both up to standard, the compressive strength of the dried pellets and the metallized pellets is low and cannot meet the transportation requirements during the titanium slag production process.

[0166] Comparative Example 6

[0167] The difference between this comparative example and Example 1 is that in this comparative example, 9 kg of titanium concentrate is mixed with 80 g of binder, and no anthracite is added during the process. The rest is the same as Example 1. The compressive strength of the obtained dried pellets is 550 N, the compressive strength of the obtained metallized pellets is 2260 N, the metallization rate is 0.87%, and the final titanium slag grade is 81.24%, and the production cycle is 120 min.

[0168] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing titanium concentrate pellets, characterized in that: The following steps are involved: (a) mixing titanium concentrate and a carbonaceous reducing agent to obtain a mixed material; The carbonaceous reducing agent is at least one of anthracite, blue charcoal and coke; (b) mixing the mixed material of step (a), a binder for titanium concentrate briquetting and water, and briquetting to obtain the titanium concentrate pellets; The binder for titanium concentrate briquetting comprises the following components: Cellulose polymer, polyvinyl acetal, and sodium alginate; The mass ratio of cellulose polymer, polyvinyl acetal and sodium alginate is 40~60:5~15:10~30.

2. The method for preparing titanium concentrate pellets according to claim 1, characterized in that: In step (a), the mass ratio of the titanium concentrate to the carbonaceous reducing agent is 90:10-25.

3. The method for preparing titanium concentrate pellets according to claim 2, characterized in that: The proportion of particles smaller than 0.075 mm in the titanium concentrate is greater than 70%.

4. The method for preparing titanium concentrate pellets according to claim 1, characterized in that: The carbonaceous reducing agent is anthracite; The proportion of particles smaller than 1 mm in the anthracite is greater than 80%.

5. The method for preparing titanium concentrate pellets according to claim 1, characterized in that: In step (b), the mass ratio of the mixed material to the binder for briquetting titanium concentrate is 100:0.4-1; The water accounts for 5% to 9% of the mass of the mixed material.

6. The method for preparing titanium concentrate pellets according to claim 1, characterized in that: The mass ratio of the cellulose polymer, polyvinyl acetal and sodium alginate is 50:10:20; The cellulose polymer is at least one of carboxymethyl cellulose, carboxyethyl cellulose and hydroxypropyl cellulose; The polyvinyl acetal is at least one of polyvinyl formal, polyvinyl acetal and polyvinyl butyral.

7. The method for preparing titanium concentrate pellets according to claim 1, characterized in that: The equipment for pressing balls is a high-pressure ball press; The process parameters of ball pressing are as follows: Output 1~3t / h; Roller surface pressure 20~30Mpa; Pressure holding time 0.5~1s.

8. A metallized pellet, characterized in that: The titanium concentrate is obtained by roasting titanium concentrate pellets prepared by the preparation method according to any one of claims 1 to 7.

9. The metallized pellets according to claim 8, characterized in that: The calcination temperature is 900-1300° C., and the calcination time is 0.5-2 hours.

10. The metallized pellets according to claim 9, characterized in that: The step of drying the titanium concentrate pellets is also included before roasting; The drying temperature is 120-180° C., and the drying time is 0.5-2 h.

Citation Information

Patent Citations

  • Pelletizing method of ilmenite concentrates and pellet binder

    CN101649392B

  • Titanium slag smelting method

    CN102399994B

  • Binder composition for pelletizing titanium concentrate and preparation method of titanium concentrate pellets

    CN103898317B

  • A production process for high-strength carbon-containing titanium concentrate pellets

    CN108374084B

  • Pelletizing method of ilmenite concentrates and pellet binder

    CN101649392A